Implementing a chatbot to promote hereditary breast & ovarian cancer genetic screening in women’s health: identifying barriers and facilitators to screening adoption - Easton N. Wollney; Shireen Madani Sims; Luisel J. Ricks-Santi; Elizabeth Eddy; Daniel Wiesman; Carla L. Fisher (BMC Public Health)
Abstract Background To promote genetic screening among women at risk for hereditary breast and ovarian cancer (HBOC), the American College of Obstetricians and Gynecologists recommends that risk assessment be integrated into practice. Chatbots like the Genetic Information Assistant (Gia®) are increasingly implemented to expand access to hereditary genetic screening. Factors that impact chatbot implementation for HBOC risk screening and women’s uptake are not fully realized. To refine implementation strategies prior to full scale implementation, we sought to identify women’s perceived facilitators/barriers to adopting Gia screening in a rural population within a large healthcare system in the southern United States. Methods We recruited both women who agreed to screen using Gia (and then recommended for genetic testing based on National Comprehensive Cancer Network guidelines) as well as women who opted not to do the screen from three Women’s Health clinics (OB/GYN) in a northern rural region of Florida. We conducted in-depth, semi-structured interviews with 17 women (nine adopted the screen, eight did not). We conducted a thematic analysis to identify and further define barriers/facilitators to women’s uptake of Gia for HBOC cancer risk screening in obstetrics/gynecology care. Results Women identified six factors that inhibited and/or facilitated their willingness to use Gia for screening: 1) cancer risk perception, 2) communication with their clinician, 3) feasibility of screening, 4) fiscal and insurance concerns, 5) technology trust/distrust, and 6) previous genetic testing experience. Findings illustrate how each factor functioned as a facilitator and/or barrier in women’s uptake (e.g., technology being trusted for accuracy versus concerns for data privacy and security). Conclusions While chatbots can extend women’s cancer risk screening access, particularly in rural regions and with college-educated women, systems-level (cost) and individual-level factors (perceived risk, misconceptions about repeating genetic testing) should be addressed to promote adoption. Women’s interaction with a clinician may be a key implementation strategy for addressing these factors to personalize the screening opportunity and promote their chatbot screening adoption.